Pengaruh Close Friend Terhadap Self-Disclosure Generasi Z Di Yogyakarta - Siti Lailatul Nur Faizah; Vanessa Adinda Putri; Wulan Guritno (GLOBAL SCIENTS PUBLISHER, 2026)
Instagram is a very popular social media platform among teenagers, providing various features, one of which is close friends. Close friends is a feature that is beneficial for Generation Z in terms of self-disclosure. Therefore, this study aims to determine whether close friends have an effect on self-disclosure among Generation Z in Yogyakarta. The population in this study was Generation Z in Yogyakarta, totaling 941,311 people, while the sample used was calculated using the Slovin formula with a percentage of 5%, resulting in a total of 115 respondents. The data collection method used was a questionnaire about Close Friends on Instagram and self-disclosure, which had been modified by the researcher. This study used a quantitative research method. The data obtained was analyzed using SPSS software. The results of this study indicate that there is a relationship between close friends on Instagram and openness among Generation Z in Indonesia. The magnitude of this influence is 9.9%, meaning that the remaining 90.1% is influenced by other variables that were not examined in this study.